Edukasi Pencegahan Hepatitis Pada Anak Sekolah dan Cuci Tangan Bersih di SD Negeri 174567 Pancurnapitu Kabupaten Tapanuli Utara Tahun 2022 - Paruhum Tiruon Ritonga; Urhuhe Dena Siburian; Enda Harani Siregar (Publikasi Indonesia, 2022)
Pregnant women have a low immune system, making them more susceptible to illness or infection. Pregnant women have an increased risk of becoming severe if infected with Covid-19, especially for pregnant women with certain medical conditions. So you have to get vaccinated against Covid-19. The thing that needs to be reminded is that giving the Covid-19 vaccine does not fully protect pregnant women from the Corona virus. Therefore, pregnant women still need to implement health protocols, so that the risk of pregnant women being exposed to Covid-19 can be minimized. Participants in the activity were 60 people who were taken randomly from 5 classes, 6 people each. To find out the increase in knowledge of elementary school children, a pretest and posttest were held. Implementation of activities in February to June 2022. The output of this community service implementation is scientific articles published in national scientific journals and IPR. The target is to increase the knowledge of elementary school children about preventing hepatitis, teaching hand washing and maintaining health protocols. Based on the results of the pre test and post test, there was an increase in the number of students who had good knowledge from 8 people (27 to 17 people (56%) after the post test. With sufficient knowledge from 12 people (40%) in the post test to 11 people (36%). Students who have less knowledge than 10 people (33%) become 2 people (8%). In the implementation of clean hand washing, students who previously did not understand how to wash their hands properly and were able to carry out how to wash their hands according to what was taught by the Service Team, namely